A Review on Orthogonal Frequency Division Multiple Access (OFDMA) in Broadband Wireless Access - Khan, A.S.; Fauzi, A.H.; Thangaveloo, R.; Julahi, A.A.; Tarmizi, S. (IJAERA, 2015)
OFDMA is the basis of future broadband access, due to its many inherent advantages such as scalability and fine granularity for multi-user access. OFDMA is a multi-user version of the popular Orthogonal Frequency-Division Multiplexing (OFDM) digital modulation scheme. Multiple accesses are achieved in OFDMA by assigning subsets of subcarriers to individual users. The purpose of this paper is to review on Orthogonal Frequency Division Multiple Access (OFDMA) in broadband wireless access. The review analysis is purely based on OFDMA Uplink system, OFDMA Cognitive Radio Networks, OFDAM cellular networks and the OFDMA interference. Some of the challenges faced in a multi-carrier OFDM/OFDMA system are dynamic resource allocation which requires the exact knowledge of channel status that is not always easy to be obtained. This paper reviewed a wide range of challenges faced by OFDMA and their suggested solutions extensively. Apart from that a thorough comparison analysis between different techniques is studied and presented in this paper.